Association of interleukin polymorphisms and inflammatory markers with hospitalization, survival, and COVID-19 severity in type 1 diabetes patients: A multivariate and Cox regression analysis: Association of interleukins with COVID-19 in T1D patients - Abdullah, Mohammed Yousif; Alhaddad, Farah Abdulkhaleq Khattab; Pambuk, Chateen Izaddin Ali; Marghali, Sonia (Cellular and Molecular Biology, 2025)
This study investigates the association between interleukin polymorphisms (IL-6, IL-10, IL-12A, and IL-18), inflammatory markers, and COVID-19 severity in Type 1 diabetes (T1D) patients. A prospective observational study enrolled 80 female T1D patients hospitalized with COVID-19 and a control group of 30 females without COVID-19. Significantly higher cytokine levels were observed in COVID-19 patients (IL-6: 64.1 ± 30.1 pg/mL, IL-10: 11.7 ± 5.8 pg/mL, IL-12A: 6.7 ± 2.9 pg/mL, IL-18: 195.4 ± 60.7 pg/mL) compared to controls (all p < 0.001). Genotype analysis revealed that the IL-6 GG and IL-18 TG genotypes were associated with elevated cytokine levels, prolonged hospitalization, and increased mortality risk (hazard ratios [HR]: IL-6 GG: 1.25, IL-18 TG: 1.30). ROC analysis indicated IL-18 (AUC: 0.88) and IL-6 (AUC: 0.84) as strong predictors of hospitalization. Cox regression showed that IL-6 and IL-18 levels significantly affected hospitalization duration and survival, while IL-12A displayed a protective effect (HR: 0.92). Kaplan-Meier analysis confirmed shorter survival for the IL-6 GG and IL-18 TG genotypes, supporting the prognostic role of cytokine levels and genotypes in COVID-19 management. This study highlights the potential of interleukin polymorphisms as biomarkers for COVID-19 severity in T1D patients.